2016
DOI: 10.1021/acs.iecr.6b02565
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of pH-Responsive Nanoscale Hydrogels for the Oral Delivery of Hydrophobic Therapeutics

Abstract: About 70% of pharmaceutical drug candidates are poorly soluble and suffer from low oral bioavailability. Additionally, a large number of therapeutics are also substrates for P-glycoprotein (P-gp) receptors present on the intestinal cell lining and undergo efflux that further reduces their oral bioavailability drastically. Nanoscale hydrogels are promising candidates for oral delivery of hydrophobic therapeutics as they hold immense potential in improving solubility and increasing intestinal permeability of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In addition to oral insulin, many stimulus-responsive systems have been designed for the treatment of other diseases such as Helicobacter pylori [ 256 ], various cancers [ 257 , 258 , 259 ]. For example, Oupciky et al reported a nanostructured lipid carrier (NLC)-based PTT formulation that can be orally administered.…”
Section: Applications Of Stimulus-responsive Systemsmentioning
confidence: 99%
“…In addition to oral insulin, many stimulus-responsive systems have been designed for the treatment of other diseases such as Helicobacter pylori [ 256 ], various cancers [ 257 , 258 , 259 ]. For example, Oupciky et al reported a nanostructured lipid carrier (NLC)-based PTT formulation that can be orally administered.…”
Section: Applications Of Stimulus-responsive Systemsmentioning
confidence: 99%
“…As shown in Figure 2A an increase in particle diameter from 103.1 nm to 134.5 nm was observed when the solution pH was increased above 5 which is close to the pKa of MAA. A swelling transition at pH 5 indicates that drug release as a result of decomplexation would occur in the upper small intestine [47,48]. Measurements of the effective surface ζ-potential of the P(MAA-g-EGco-tBMA) nanoparticles revealed a decrease in charge at pH 5 when the particles being to swell ( Figure 2B).…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…The tetra-arm epoxy cross-linker (EC), [33] PEGdiamines (2 kDa, 4 kDa), [34] and rhodamine-NH 2 (RHB-NH 2 ) [35] were synthesized according to reported procedures. 1 H NMR spectra were recorded on Varian Mercury VX (400 MHz) spectrometer using CDCl 3 or DMSO as the solvent and tetramethylsiliane as the internal reference. Surface morphology of the hydrogels was examined by scanning electron microscopy and energy dispersive X-ray (EDX) studies.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Synthesis of multifunctional hydrogels responsive to various external stimuli by change in color, shape, or volume has many potential applications in several areas such as controlled drug delivery systems, wound healing dressings, cell scaffolds, or environmental applications . It is important that the synthetic approaches to such materials are simple enough to warrant widespread adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation